One out of four patients with pancreatic cancer experience psychological symptoms: A systematic review and meta-analysis - Anna Sára Bognár; Dóra Andrea Sükös; Cristina Patoni; Eszter Ágnes Szalai; Brigitta Teutsch; Dániel Sándor Veres; Nóra Hosszúfalusi; Bálint Mihály Erőss; Katalin Márta; Péter Hegyi (PLoS ONE, 2026)
The death rate from pancreatic cancer is one of the highest of all cancers, with increasing incidence every year over the past decades. As the prognosis remains extremely poor, this trend brings not only a growing clinical challenge, but also a significant psychological toll for patients. In comparison to other types of cancer, our understanding of the psychological burden of such a deadly disease is still limited. Recognizing and addressing the psychological aspects of pancreatic cancer are crucial for comprehensive patient care. We, therefore, aimed to quantify the psychological burden of patients with pancreatic cancer. We conducted a systematic search (PROSPERO: CRD42022288805) of MEDLINE, Cochrane, and Embase databases to identify articles reporting on the prevalence of psychological symptoms among patients with pancreatic cancer. The symptoms examined were depression, anxiety, distress, fatigue, sleep disturbances. Study quality for the included studies was assessed using the Joanna Briggs Institute tool. Relevant data were extracted and exported for quantitative synthesis. The meta-analysis of the proportion of symptoms with a 95% confidence interval (CI) was conducted using frequentist random-effects models. Subset analyses were performed based on the severity of depression. A total of 28 articles were included in the meta-analysis and 31 in the systematic review. Our results showed that the proportion of depression (19 studies; 78,930 patients) was 0.27 (95% CI: 0.18–0.39). The proportion for anxiety (18 studies; 26,538 patients) was 0.29 (95% CI: 0.16–0.46; for distress (6 studies; 2746 patients) 0.43 (95% CI: 0.25–0.63); for fatigue (7 studies; 11 338 patients) 0.40 (95% CI: 0.21–0.63); and for sleep disturbances (3 studies; 10,645) 0.31 (95% CI: 0.06–0.77). These findings highlight the urgent need to integrate psychological care into pancreatic cancer treatment. Future research should explore sources of heterogeneity to better identify which approaches provide the most psychological benefit and tailor interventions to patient needs accordingly.